Dampak Latihan Kondisi Fisik Terintegrasi Terhadap Peningkatan Biomekanika dan Efektivitas Smash Bulutangkis Remaja di Klub Kota Makassar - Muhammad Ishak; Syahruddin; Sahabuddin; Muh. Adnan Hudain (Bulletin of Community Engagement, 2026)
The smash is a key attacking technique in badminton, heavily influenced by the athlete's biomechanical efficiency and physical fitness. However, at the youth level, club training programs are often fragmented and do not systematically integrate the development of explosive strength, core stability, and neuromuscular coordination. This study aims to analyze the impact of integrated physical conditioning training on improving biomechanical parameters and smash effectiveness in youth badminton athletes at a Makassar City club. The study used a quasi-experimental design with a randomized pretest-posttest control group design. The sample size was 60 athletes (30 experimental and 30 control). The intervention was conducted for 8 weeks, administered three times per week. The variables measured included trunk rotation, shoulder angular velocity, racket head velocity, shuttlecock speed, smash accuracy, vertical jump, core stability, and agility. Data were analyzed using t-tests and effect size (Cohen's d) at a significance level of 0.05. The results showed significant improvements in the experimental group: trunk rotation (+17.7%), shoulder angular velocity (+17.0%), racket-head velocity (+18.5%), shuttlecock speed (+14.4%), and smash accuracy (+36.5%) (p < 0.05; large effect size). There was a strong correlation between increases in vertical jump and racket-head velocity (r = 0.72). It was concluded that integrated physical conditioning training effectively improves biomechanical efficiency and smash performance in adolescent athletes and is recommended in evidence-based coaching models.